EFFECT OF ORDER-DISORDER TRANSFORMATION MODES ON THE ANOMALOUS YIELD BEHAVIOR OF FE3AL INTERMETALLIC COMPOUNDS - PARK, JW; MOON, IG; YU, J (CHAPMAN HALL LTD, 1991)
Compression tests were performed to clarify the effects of transformation modes on the anomalous yield behaviour of hypo- and hyper-stoichiometric Fe3Al alloys which show a first- and a second-order transition, respectively. There were great differences in the anomalous yield behaviour depending on the transformation modes. In the first-order transformation alloy, changes in the degree of order played an important role before phase separation, while precipitation of alpha phase had a great influence on the anomalous behaviour after phase separation. In contrast, only the change in the degree of order was a dominant factor in the second-order transformation alloy.
Keywords: IRON-ALUMINUM ALLOYS; FE-AL ALLOYS